Analiza poškodb pri cheerleadingu - Čeklić, Urška (Šport (Ljubljana), 2022)
Extensive research has been conducted in the United States on injuries in cheerleaders. Yet, we do not know how injuries occur in Slovenian cheerleaders. The study included 56 participants from different categories of cheerleading. We determined the incidence rate of injuries, the occurrence of acute or chronic injuries, the risk factor and location of injuries. On total of 153 injuries were observed in 292 hours of cheerleading, with an incidence rate of 2.9 injuries per 1000 hours. Statistically significant differences were observed for acute and chronic injuries between categories in cheerleading (p <0.001). The most common risk factor for injury was reported to be landing and falling, while ankle and knee were the most common sites of injury. Considering characteristics of reported injuries in the present study and the fact that the level of coach qualification is one of the most important risk factors for injuries indicates the need for proper education of coaches and the introduction of quality injury prevention into the training process
Keywords: cheer ples; dejavniki tveganja; epidemiologija; mišičnoskeletni sistem; ples; šport; športne poškodbe